Do Environmental Risks Explain the Sovereign Sukuk Yields in Malaysia? - Mohamad Shafi, Roslina; Shaharuddin, Norhasimah; Bakar, Norsaliza Abu; Muhamat, Amirul Afif; Tabash, Mosab I. (The Indonesian Capital Market Review, 2025)
Given the increasing risks posed by environmental degradation, severe climate change, and recent pandemics, the establishment of a sustainable economy has become a priority for numerous nations. From this perspective, it is crucial to emphasize sustainable finance since it has the potential to serve as a vehicle for accomplishing a green economic agenda. Sovereign sukuk held a prominent position in the sukuk market, both domestically and internationally, but its influence was particularly significant inside the domestic sphere. The study seeks to examine the link between environmental risks and the yield performance of sovereign sukuk. Sukuk performed less favourably compared to other asset classes in terms of including environmental risk in the calculation of yield. Therefore, it is crucial to conduct additional investigation into the impact of environmental concerns on sukuk yields. The analysis includes Ordinary Least Squares (OLS) and quantile regression techniques, using data from the period 1990-2021. This study examines the relationship between market variables, environmental risk, and sukuk yields in Malaysia. The paper demonstrates that both market variables and environmental concerns have an impact on the yields of sovereign sukuk. Additionally, it introduces a novel approach for modelling these yields.